Dapatkah Efikasi Diri Memediasi Pengaruh Kompetensi Kejuruan Terhadap Kesiapan Kerja Siswa di Bidang Akuntansi ? - Ananda Gilang Ismoyo; Eko Wahjudi (Jurnal Pendidikan Akuntansi (JPAK), 2023)
The purpose of this research is to prove the role of self-efficacy as a mediator between vocational competence and work readiness in grade 12 students of SMKN Mojoagung in the 2022/2023 academic year. This type of research is explanatory with a quantitative approach. Primary data collection in this research uses a questionnaire. Processing and analysis of data in this research using SEM-PLS analysis. The results of this research indicate that vocational competence cannot directly influence work readiness, self-efficacy can directly influence work readiness, self-efficacy is directly influenced by vocational competence, self-efficacy can be a mediating variable between vocational competence and work readiness in class 12 AKL students at SMKN Mojoagung for the academic year 2022/2023. In this research self-efficacy acts as a full mediation. For further researchers, it is hoped that they can expand the sample in one district or wider to strengthen the research findings , increase the variables studied such as family support, career maturity and time, and can be add the test for instrument development.